2016
DOI: 10.1007/s00216-016-9314-5
|View full text |Cite
|
Sign up to set email alerts
|

NanoESI-MS-based lipidomics to discriminate between cultivars, cultivation ages, and parts of Panax ginseng

Abstract: Korean ginseng (Panax ginseng C.A. Meyer) is one of the most popular medicinal herbs used in Asia, including Korea and China. In the present study lipid profiling of two officially registered cultivars (P. ginseng 'Chunpoong' and P. ginseng 'Yunpoong') was performed at different cultivation ages (5 and 6 years) and on different parts (tap roots, lateral roots, and rhizomes) using nano-electrospray ionization-mass spectrometry (nanoESI-MS). In total, 30 compounds including galactolipids, phospholipids, triacylg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 77 publications
1
10
0
Order By: Relevance
“…PLS-R represents the relationship between two X and Y groups of a PLS model and interprets the model to predict Y by analyzing X ( Abdi, 2003 ; Eriksson et al ., 2006 ). To validate the PLSR model, a cross-validation is first performed to determine the suitability of the model ( Eriksson et al ., 2006 ; Kim et al ., 2016 ). R 2 Y is a parameter that represents the goodness of fit and indicates how close the values from the PLSR are to the actual values.…”
Section: Multivariate Statistical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…PLS-R represents the relationship between two X and Y groups of a PLS model and interprets the model to predict Y by analyzing X ( Abdi, 2003 ; Eriksson et al ., 2006 ). To validate the PLSR model, a cross-validation is first performed to determine the suitability of the model ( Eriksson et al ., 2006 ; Kim et al ., 2016 ). R 2 Y is a parameter that represents the goodness of fit and indicates how close the values from the PLSR are to the actual values.…”
Section: Multivariate Statistical Analysismentioning
confidence: 99%
“…Quality control of herbal extracts is a challenging endeavor because they usually contain numerous phytochemicals ( Kim et al ., 2016 ). Furthermore, multivariate statistical analyses are needed to reduce the complexity of the data from metabolic profiling and facilitate the detection of the pattern of changes related to the environmental or genetic factors in metabolite compositions.…”
Section: Multivariate Statistical Analysismentioning
confidence: 99%
“…2B), where VT3P/RR (A4177G3-RIB) expressed higher total PI, PC and HexCer lipid concentration followed by VT2P (DKC26-28RIB, DKC23-17RIB) and RR2 (Yukon-R, Fusion-RR). Kim et al (2016) reported that out of 30 lipid molecular species, triacylglycerol TG(54:6), phosphatidylglycerols (34:3), monogalactosyldiacylglycerol MGDG(36:4) and PA(36:4, 34:1) could successfully discriminate the different genotypes based on plant ages and plant parts in Panax ginseng L. Similarly, in the current study, we observed that PI, PC and HexCer root membrane lipids could be used as a potential biomarker to discriminate five silage-corn genotypes possessing different value-added genetic traits necessary for plant protection when grown under field conditions in boreal climate ( Fig. 2A,B).…”
Section: Pi Pc and Hexcer Lipid Classesmentioning
confidence: 99%
“…Concomitant with genotypic expression, endogenous or induced production of membrane lipids has also been reported to be part of the successful strategy associated with plant acclimation in specialized growth conditions or environments (Nadeem et al 2019b(Nadeem et al , 2019c. Kim et al (2016) demonstrated that different molecular species of triacylglycerol, phosphatidylglycerol, monogalactosyldiacylglycerol and phosphatidic acid could be used as biomarkers to discriminate Panax ginseng L. cultivars, as well as their cultivation age. Authors further demonstrated that using the predicted model approach, unknown samples of Panax ginseng L. could be successfully identified.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Kim et al 35 extracted lipids using Matyash et al's method 36 with methyl-tert-butyl ether/ methanol/water (10:3:2.5, v/v/v). The intact species of TAGs and MGDG from ginseng lipid extract were analyzed using direct infusion (DI)-MS by untargeted approach.…”
mentioning
confidence: 99%